Vpliv rastiščnih in sestojnih razmer na pestrost tal in vegetacije v izbranih bukovih in jelovo-bukovih gozdovih na Kočevskem - Kutnar, Lado (Zbornik gozdarstva in lesarstva, 2006)
In four research complexes in the Kočevje region, the biodiversity of forest soil conditions and vegetation have been studied. Two of them were in Dinaricfi r-beech forest (Omphalodo-Fagetum association) in the area of Kočevski Rog. Two complexes (Predinaric mountain beech forest of Lamio orvalae-Fagetum association and acidophilic beech forest of Blechno-Fagetum association) were selected south of Kočevje, near Kočevska Reka. The complexesconsisted of 11 objects in various site and stand conditions, and these of 60 research plots. In the fi rst three complexes established on limestones and dolomites, six soil units (Folic, Lithic, Eutric and Rendzic Leptosols, Eutric Cambisols and Haplic Luvisols) and nine humus groups of three humus forms were determined. In the forth complex formed on sandstones and claystones, only one soil unit (Dystric Cambisols) but seven humus groups of three humus forms were found. A total of 165 vascular plants and bryophytes were found. On research plots on limestones and dolomites, almost three times higher number of plant species were established than on sandstones and claystones. The analysis shows a signifi cant difference between the selected research objects (e.g. open stand gaps vs. closed foreststand, gaps in virgin forest remnant vs. man-made gaps in managed forest, steep rocky slopes vs. plateaus, sinkholes). The specifi c fl oristic composition is mostly a result of different stand and sites situations, especially soil conditions, and of the past and current forest management.
Keywords: biotska raznovrstnost; dinarski gozd; gozdna tla; jelovo-bukovi gozdovi; Slovenija; vegetacija